4CPS-096 Effectiveness, safety and potential interactions of elbasvir/grazoprevir for chronic hepatitis c infection. (2nd March 2018) - Mensa, M; Sotoca, JM; Codina, C
Abstract : Background: Elbasvir/grazoprevir is a newly direct-acting antiviral combination indicated for the treatment of chronic HCV genotype 1 or 4 infection in patients with and without compensated cirrhosis. Purpose: Our aim was to assess the effectiveness, safety and potential interactions of elbasvir/grazoprevir treatment in patients with HCV infection in routine clinical practice. Material and methods: Observational retrospective study in a tertiary hospital. Monoinfected adult patients with HCV infection treated with elbasvir/grazoprevir in monotherapy between January and June 2017 were registered. Age, sex, ethnicity, hepatic fibrosis stage, prior HCV treatments, regular medication, adverse events (AE), HCV genotype, viral load (VL) at baseline, at treatment completion and 12 weeks after the end of treatment (EOT) were collected. Achieving sustained virologic response (SVR12), defined as undetectable HCV-RNA 12 weeks after treatment completion, was considered effective. Results: Sixty patients (63±12 years, 57% females, 97% Europeans) completed treatment. Forty patients (66.7%) were naïve. HCV genotype was 1b in 53 patients (88%) and 4 in seven patients. The degree of fibrosis was F0 to F1 in 13 patients(21.7%), F2 in 22 (36.7%), F3 in 13 (21.7%) and F4 in 12 (20%). Forty-nine patients (82%) were regularly taking medication with an average of five drugs per patient. Potential interactions were detected in 13 patients (21.7%), mostly with amlodipine (n=4), statins (n=4), amiodarone (n=3), tacrolimus (n=2) and colchicine (n=2). VL was undetectable in 57/60 patients (95%) at the EOT. Treatment outcomes were available for 42 patients. Global SVR12 was achieved by 39/42 patients (92.9%). Three patients failed to achieve SVR12: two, with genotype 1b, had viral breakthrough (one of them was reanalysed and found to be 1a) and one discontinued due to renal transplant complications. Twenty-nine patients (48.3%) reported AE. Most described AE were gastrointestinal disorders (n=8), arthralgia/myalgia (n=7), asthaenia (n=6), headache (n=4), pruritus (n=3), alopecia (n=3) and insomnia (n=2). Laboratory abnormalities were found in two patients, one with an increase in lipase and another with an increase in amylase and lipase values. Conclusion: Elbasvir/grazoprevir was effective and similar results of SVR12 were obtained in clinical trials. Adverse events were reported by approximately half of all patients. Elbasvir/grazoprevir may have clinically significant interactions. References and/or Acknowledgements: Elbasvir/grazoprevir: Summary of product characteristics. EMA. No conflict of interest